1993
DOI: 10.1016/s0006-3495(93)81343-2
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation by ionizing radiation of ion channels formed by polyene antibiotics amphotericin B and nystatin in lipid membranes: an inverse dose-rate behavior

Abstract: The phenomena reported are part of a study about the effects of ionizing radiation on membrane transport. We found that the conductance of lipid membranes in the presence of the polyene-antibiotics nystatin or amphotericin B is reduced to virtually zero following irradiation. Ion channels formed by these substances seem to represent extremely sensitive structures being inactivated by radiation doses in the range of a few Centigray (1 cGy = 1 rad) at sufficiently small dose rates. Inactivation shows a so-called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Consequently the radical chain mechanism represented by Eqs. 2-5 shows the same dose rate dependence as was observed previously at the inactivation of polyene channels [20] and is now reported for the inactivation of the Na/K-ATPase (Fig. 3).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consequently the radical chain mechanism represented by Eqs. 2-5 shows the same dose rate dependence as was observed previously at the inactivation of polyene channels [20] and is now reported for the inactivation of the Na/K-ATPase (Fig. 3).…”
Section: Discussionsupporting
confidence: 86%
“…3). This is similar to the inactivation of ion channels formed by the polyene antibiotics amphotericin B and nystatin in planar lipid membranes [20]. An increase in the sensitivity by 2-3 orders of magnitude has been observed in that case at sufficiently small dose rates.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We have previously shown that inactivation of polyene channels shows an inverse dose-rate behaviour similar to that of radiation-induced lipid peroxidation (Barth et al 1993) . We intended to provide a more detailed analysis of the radicals involved and of the mechanism of inactivation .…”
Section: Introductionmentioning
confidence: 89%
“…1 or 1 mol dm -3 NaCl typically), which were prepared across a hole in a PTFE wall (Lauger 1985) . For further experimental details, as well as for a description of the apparatus used for irradiation by 80-kV X-rays of the membrane and its aqueous environment, the reader should consult Stark (1991), Barth and Stark (1991), and Barth et al (1993) . The presence of cholesterol (or of ergosterol) is required to ensure the presence of open ion channels by the polyene antibiotic amphotericin B Holz 1973, De Kruijff andDemel 1974) .…”
Section: Methodsmentioning
confidence: 99%